(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the basics of the formation of basic knowledge and skills of graduates of pedagogical higher education institutions in the implementation of interdisciplinary links in secondary schools, as well as the content and essence of interdisciplinary links in the study of natural sciences at school.